Digital innovation: navigating change with flexibility and speed - Morton, Josh (Henry Stewart Talks, 2024)
What is digital innovation?, Why does digital innovation matter?, A framework for digital innovation, Artificial Intelligence and Machine Learning, Blockchain technology, Internet of Things (IoT) and Big data, Virtual reality (VR) and the metaverse